Pengaruh Harga, Lokasi, Store Atmosphere, dan Word Of Mouth terhadap Keputusan Pembelian pada Warung Gunung (Wagu) Kediri - Syahrul Syaiful Riza; Djunaedi; Sasi Utami (Politeknik Raflesia Press, 2026)
-This research aims to determine the influence of price, location, store atmosphere, and word of mouth on purchasing decisions among consumers of Warung Gunung (Wagu) Kediri. This type of research uses quantitative methods, namely a method that describes in detail the object of research. The population in this study were all consumers who had visited Warung Gunung (Wagu) Kediri during the last 6 months. Meanwhile, the sample was 60 people/respondents. Data collection methods use questionnaires, observation, documentation and literature study. Meanwhile, the data analysis method uses validity and reliability tests, classical assumption tests, multiple linear regression tests, partial significance tests (statistical test (t), simultaneous significance tests (F statistical test), and coefficient of determination. From the results of this research it can be concluded that: (1) Price partially has a significant relationship with purchasing decision variables (2) Location has a significant positive effect on increasing purchasing decisions (3) Store Atmosphere has a significant positive effect on purchasing decisions mouth does not have a positive effect on increasing purchasing decisions (5) Price (X1), location (X2), Store Atmosphere (X3) and word of mouth (X4) together (simultaneously) have a significant relationship to the dependent variable, namely decision. purchases (Y). The research results show an adjusted R square of 0.775 or 77.5%. This shows that there is a correlation between purchasing decisions and the variables price (X1), location (X2), Store Atmosphere (X3) and word of mouth ( X4) is high.